Simulation and modelling of spray characteristics, spray penetration length and injection pressure of biodiesel - Mohd Yaacob, Nur Syuhada; Khalid, Amir; Jaat, Norrizam; Rhaodah Andsaler, Adiba; Azizul, Muhamad Asri; Sapit, Azwan (2024)
This research compare three different types of Crude Palm Oil (CPO) biodiesel blends, B5, B10, and B15 with different ambient density on nozzle flow and spray characteristics by using CPO and simulated the physics flow pattern of mixture formation with tangential velocity between biodiesel, diesel fuel, and air in the mixing chamber of RCM, to determine the nozzle flow and spray characteristics for different injection pressure of biodiesel spray to ambient variant conditions on mixture formation. In order to mimic the spray processes, an Eulerian-Lagrangian multiphase technique is presented in this study. This work makes use of Computational Fluid Dynamics (CFD) Fluent to examine the spray properties of biodiesel fuels, and the simulation took biodiesel injection into the constant volume chamber of the RCM into account. The boundary condition is set up at a distinct ambient parameter. The presence of in-cylinder flow, the impact of fuel type, injection pressure, and ambient variables on spray behaviour, such as spray penetration, had been examined. Analysis of the spray penetration variation with time for various ambient parameters and different types of biodiesel fuels revealed that the biodiesel fuels were predicted to develop their break-up more quickly due to the fact that all fuels atomize more quickly in the presence of higher injection pressures. The effects of these various parameters were examined in terms of spray characteristics and contrasted with the findings of the experiments